Unlocking the Power of Event Sponsorship: How Attitudes and Brand Image Fuel Purchase Intentions - Reyhana Zahra Zain; Karto Adiwijaya (CV. Syntax Corporation Indonesia, 2024)
Event sponsorship, as part of promotion, offers opportunities for brands to increase visibility through involvement in events that match the interests of the target audience. The method used in this research is quantitative method and will be analyzed with the Structural Equation Model (SEM). The target of this research is the audience of the Reality Club Concert which is presented in Jakarta sponsored by the Kapal Api brand. The sampling method is a non-probability sampling technique with a convenience sampling approach, then continued with a snowball sampling approach which is carried out by relying on personal contacts taken from the results of the previous approach, namely the results of convenience sampling. total respondents were 200 in this study. This study found that sponsor-event congruence significantly improved brand image and attitude toward sponsor, which in turn, improved purchase intention. In contrast, involvement and exposure to the sponsored event had no significant influence on attitude towards the sponsor. Based on the results of the study, it can be concluded that involvement and exposure to sponsored events do not have a significant effect on attitudes towards sponsors. However, sponsor-event congruence has a positive and significant influence on attitude towards the sponsor and brand image. In addition, brand image also has a positive and significant impact on attitude towards the sponsor. Finally, attitude towards sponsor and brand image have a positive and significant influence on purchase intention in the case study of Brand Kapal Api at Reality Club Concert.